Basis of ACCase and ALS inhibitor resistance in Hordeum glaucum Steud. Issue 8 (15th February 2017) - Shergill, Lovreet S; Malone, Jenna; Boutsalis, Peter; Preston, Christopher; Gill, Gurjeet
Abstract: BACKGROUND: Acetyl coenzyme‐A carboxylase (ACCase) and/or acetolactate synthase (ALS) inhibitor resistance has been identified by herbicide resistance screening in eight populations obtained from cropping regions of South Australia. This study aimed to quantify the level of resistance and characterise the molecular basis of resistance to ACCase and ALS inhibitors in these H. glaucum populations. RESULTS: H. glaucum populations from the Upper‐North region were highly resistant (resistance index RI > 12) to the aryloxyphenoxypropionate (APP) herbicides quizalofop and haloxyfop and less resistant (RI = 2–12) to cyclohexanedione (CHD) herbicide clethodim, and some Mid‐North populations had a low level of resistance (RI = 2–6) to the sulfonylurea (SU) herbicide mesosulfuron. Gene sequencing confirmed the presence of Ile‐1781‐Leu, Ile‐2041‐Asn and Gly‐2096‐Ala mutations in the ACCase gene, with no mutation found in the ALS gene. The use of the known metabolic inhibitor malathion in combination with mesosulfuron enhanced the activity of this herbicide. These populations were also susceptible to SU herbicide sulfometuron. CONCLUSION: This study has documented APP‐to‐CHD herbicide cross‐resistance, the first case of ACCase inhibitor resistance due to Ile‐2041‐Asn mutation, and characterised the resistance to ALS inhibitors in H. glaucum . Resistance to ACCase inhibitors is due to a target‐site mutation. The reversal of SU resistance by malathion and susceptibility to sulfometuron suggests that non‐target‐site mechanisms confer resistance to ALS inhibitors. © 2016 Society of Chemical Industry